1975
DOI: 10.1139/b75-207
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of infection of bean with Pythium myriotylum compared with infection with other Pythium species

Abstract: Clusters of abundant appressoria formed from branching hyphae of mycelial inoculum of Pythium myriotylum on the surface of bean hypocotyls and roots. Pythium aphanidermatum usually produced single appressoria, but sometimes small clusters of appressoria. Pythium ultimum produced only single appressoria. Early pathogenesis of all species was characterized by rapid radial growth of hyphae in the epidermal cells, which was more rapid than in the cortex. These hyphae were constricted at the host cell walls. Invade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…However, in the case of the mycelium, inoculation followed production of an infection peg. In both situations, penetration and invasion of the roots by P. myriotyium propagules was inter-and intracellular, A similar report made on the histopathology of P, myriotyium in cotton, tomato, eggplant, and bean seedlings, indicated that the hyphae moved both intercellularly and intracellularly through the cortex during advanced pathogenesis (Dow and LUMSDEN 1975).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…However, in the case of the mycelium, inoculation followed production of an infection peg. In both situations, penetration and invasion of the roots by P. myriotyium propagules was inter-and intracellular, A similar report made on the histopathology of P, myriotyium in cotton, tomato, eggplant, and bean seedlings, indicated that the hyphae moved both intercellularly and intracellularly through the cortex during advanced pathogenesis (Dow and LUMSDEN 1975).…”
Section: Discussionsupporting
confidence: 52%
“…This is the first report that detached mycelia of P. myriotyium can be induced to produce zoospores in vitro, DRECHSLER (1943) reported that zoospores were produced on undetached mycelia of P. myriotyium on maize-meal or lima bean agar medium in Petri dishes and flooded with tap water. Dow and LUMSDEN (1975) also reported that P. myriotyium zoospores were produced on infected bean hypocotyls or roots by washing the P. myriotyium culture and soaking them in tap water. The size and shape, as well as the length, of the fiagelia of zoospores of P. myriotyium were similar to earlier reports (DRECHSLER 1943, Dow andLUMSDEN 1975).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest Pythium sp. dry mycelial weight was recorded at the pH of 7.0 (386.60 mg) which is on par with the pH 6.5 (352.20 mg) and these are followed by pH 7.5 (234.50 mg), pH 6.00 (201.30 mg), pH 5.5 (191.18 mg), pH 5.0 (191.00 mg), 4.5 (155.80 mg), 8.0 (135.70 mg), 8.5 (45.00 mg) and no growth was seen at 3.5 pH, 4.0 pH and 9.5 pH Dow and Lumsden (1975) and which were white to colourless reported by Alhussaen (2019). Pathogenicity was proved by inoculating mycelial plugs of fungus Pythium sp.on wounded root of healthy mulberry plant.…”
Section: Effect Of Ph On the Growth Of Pythium Sp In Liquid Mediamentioning
confidence: 99%